2020
DOI: 10.24929/lensa.v10i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Argumentasi Ipa Siswa Melalui Pembelajaran Argumentasi Driven Inquiry (Adi)

Abstract: Penelitian ini bertujuan menganalisis pengaruh pembelajaran ADI terhadap kemampuan argumentasi IPA siswa. Metode penelitian yang digunakan quasi experiment, dan sampel penelitian ialah siswa kelas VIII yang terdiri dari 27 siswa diperlakukan pembelajaran ADI dikategorikan kelas eksperimen sedangkan 30 siswa yang diperlakukan pembelajaran konvensional dikategorikan kelas kontrol. Tes esai argumentasi gelombang digunakan sebagai instrumen pengumpulan data kemampuan argumentasi IPA siswa yang diberikan pada prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Another study by Utami et al (2022) showed an increase in the level of argumentation at pretest at level 1, namely students were only able to mention claims, then at posttest at levels 3 and 4, namely students were able to express claims, data, warrant, and backing. This is supported by research conducted by Siregar & Pakpahan (2020) which shows that the ADI learning model has a significant effect on the science argumentation abilities of junior high school students. The results of the argumentation level have increased in the experimental class to reach level 4, while the control class is dominant at levels 1 and 2 which are above 25%.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Another study by Utami et al (2022) showed an increase in the level of argumentation at pretest at level 1, namely students were only able to mention claims, then at posttest at levels 3 and 4, namely students were able to express claims, data, warrant, and backing. This is supported by research conducted by Siregar & Pakpahan (2020) which shows that the ADI learning model has a significant effect on the science argumentation abilities of junior high school students. The results of the argumentation level have increased in the experimental class to reach level 4, while the control class is dominant at levels 1 and 2 which are above 25%.…”
Section: Resultsmentioning
confidence: 53%
“…Most of the students in the ADI class were able to organize arguments strongly and correctly even reaching the highest level (level 5). This is supported by research conducted by Siregar & Pakpahan (2020) which shows that the ADI learning model has a significant effect on the science argumentation abilities of junior high school students. The results of the argumentation level have increased in the experimental class to reach level 4, while the control class is dominant at levels 1 and 2 which are above 25%.…”
Section: Introductionmentioning
confidence: 53%
“…Argumentasi ilmiah sangat diperlukan dalam pembelajaran IPA agar siswa dapat memberikan argumentasi dengan menghubungkan prinsip-prinsip dan konsep-konsep IPA untuk menjelaskan masalah atau fenomena dalam kehidupan (Siregar & Pakpahan, 2020). Argumentasi ilmiah adalah kemampuan menemukan gagasan atau ide bukti nyata yang ada dalam sains dan dengan hasil pemikiran (Zahara et al, 2018).…”
Section: Pendahuluanunclassified
“…So, argumentation ability has been used as educational standards and as criteria for assessing students (Heng et al 2015). This activity shows that argumentation ability must be realized in the learning process for students so that communication skills get better and 21st century competencies can be realized (Siregar & Pakpahan, 2020).…”
Section: Introductionmentioning
confidence: 99%